QARD-AL-HASSAN AS A TOOL FOR POVERTY ALLEVIATION: A CASE STUDY OF THE FAEL KHAIR WAQF PROGRAM IN BANGLADESH - Muneer, Farah; Khan, Foyasal (Journal of Islamic Monetary Economics and Finance, 2019)
The central focus of the Islamic economic system is on socioeconomic justice and theoverall welfare of society, especially at the bottom of the pyramid segment. Qard-al-Hassan, alongside zakat and sadaqah, is one of the instruments for the redistributionof income and wealth from the rich to the poor in Islam. In 2007, Bangladesh wasstruck by super cyclone SIDR, leaving 3,406 people dead. Moreover, SIDR causedunprecedented damage to homes, crops and livelihoods. The Fael Khair Waqf (FKW)Program came as a response to the urgent need to assist the victims of the cyclone andinitiated an interest-free micro-loan (Qard-al-Hassan) scheme to restore the livelihoodsof a large segment of the victims and to lift them out of poverty. While investigatingthe effectiveness of Qard-al-Hassan in poverty reduction, this paper also examinesthe FKW program as a case study. Analysis was conducted of 1600 households usingan independent sample t-test and logistic regression to investigate to what extent theprogram has been effective in reducing poverty. The findings of the logistic analysisare that the probability of being poor for FKW participants is around 1.46 times lowerthan for non-participants. Moreover, the Qard-al-Hassan of FKW lowers the cost ofborrowing significantly and hence participants can accumulate more assets, whichmight help them to improve their economic status. Overall, the effectiveness of theprogram implies that development practitioners and researchers should promote theoutreach of Qard-al-Hassan so that the extreme poor can easily avail themselves of theservices.